Una intención suprema - Josefa Dolores Miranda Tarragó (Editorial Ciencias Médicas, 2013)
Fidel Castro, in his plea, History will absolve me refers to the state of total abandonment in which the oral health of the majority of the Cuban population was before 1959. When referring to the future that concerned him, he said: "[ ...] at thirty they will not have a healthy piece in their mouth [...] ". This situation changed radically after the triumph of the Revolution. The stomatologists have witnessed the importance that has been given to the prevention and promotion of health, not only the treatment of the sick man. The intention has been to approach a social practice consistent with this approach. The oral health indexes reached, as shown by the oral health studies of the National Direction of Stomatology until 2010: healthy, 71% of children from 5 to 6 years of age; 91.2% of 18-year-olds retain all their teeth; 69.8% of people do not have periodontal disease; the index of decayed, filled and lost teeth CPO-D at 12 years is 1.38%; the average number of teeth lost between 35 and 44 years is 4.6%, and 16.9% between 65 and 74 years of age. The Comprehensive Stomatological Care Program and the Practical Guidelines of Stomatology are valuable documents that show all the development that stomatology has achieved in Cuba, that is why they must be available to all specialists, in the most developed stomatological centers until the more humble or remote consultation. These documents provide the stomatologist with a set of procedures that help sustain and elevate the achievements that have been achieved in relation to oral health. The supreme intention is that despite the growing population aging, older Cubans keep all their teeth healthy.